KESENJANGAN ANTARA STANDAR BAKU AKSESIBILITAS DAN PERSEPSI PENYANDANG DISABILITAS FISIK PADA RUANG TERBUKA PUBLIK TAMAN NOSTALGIA DI KOTA KUPANG (Jurnal Arsitektur ARCADE, 2026)
Public open spaces (POS) are popular places for recreation, exercise, gathering, and socializing. One of the POS that is actively visited by the people of Kupang City is Nostalgia Park. In the concept of an inclusive city, POS must be accessible to all people, including people with physical disabilities. Although accessibility standards are available in Indonesia as guidelines for creating inclusive POS, their implementation in the field has not been optimal in terms of actual user experience. This study aims to identify the extent to which the implementation of the standards of the Permen PU No. 14/PRT/M/2017 on POS elements matches the accessibility experience of users with physical disabilities at Nostalgia Park. The research method used is descriptive evaluative through observation and questionnaires. Observations use a 3-point scale converted into a percentage, while the questionnaire is calculated from the percentage of respondents who choose “agree” and “strongly agree”, then compared to see the level of accessibility suitability. The results show that the accessibility level of some POS elements does not meet technical requirements, especially ramp, signage, and parking areas. Furthermore, perceptions of people with disabilities indicate that elements that actually meet technical standards are not yet fully usable independently and comfortably. This finding indicates a gap between physical conditions and user experience, necessitating an approach to developing accessibility standards for RTP elements that is based on the user experience, particularly for people with physical disabilities.